Mechanisms for Ensuring Economic Security of the Insurance Market - Lupak Ruslan L.; Kunytska-Iliash Marta V. (Problemi Ekonomiki)
The article substantiates the key importance of ensuring economic security in the insurance market in the context of addressing tasks for strengthening stability and ensuring its sustainable operation and activating development. By using a comprehensive approach to the mechanisms of ensuring economic security in the insurance market, the institutional, financial-economic, organizational-management, informational-analytical, and social-communication aspects are included. The substantive content, tools of influence, and relevant objects of regulation are revealed, allowing for a holistic understanding of the mechanisms for ensuring economic security in the insurance market. Emphasis is placed on providing regulatory and legal support for insurance operations, financial sustainability and transparency of the activities of insurance market participants, improving the quality of internal management of insurance companies, developing digital technologies, actuarial and analytical support, as well as strengthening trust in insurance from the public and businesses. It is noted that in terms of the institutional aspect, the mechanisms include insurance companies, insurance market intermediaries, regulatory bodies, and professional associations; in the financial-economic aspect – the assets of insurers, insurance reserves, insurance premiums, and payouts; in the organizational and managerial aspect – the governing bodies of insurance companies, internal control services, underwriting operations, audits, and the human resource potential of the industry; in the informational-analytical aspect – financial and statistical reporting, information flows, databases, analytics, and actuarial calculation systems; in the social-communication aspect – interaction with policyholders, the public, target consumer groups, and the media. It is determned that the effectiveness of mechanisms ensuring the economic security of the insurance market is confirmed by their ability to increase the resilience and transparency of market relations, strengthen the trust of market participants, and promote the stable development of the insurance industry.